Stress-Controlled Dynamic Triaxial Experiments to Examine the Liquefaction Response of Clean Sand - Zeybek, Abdulhakim (My University, 2022)
Loosely packed cohesionless soils may suffer partial or complete liquefaction during seismic loading, causing significant structural damage. The dynamic behavior of liquefiable soils is widely investigated through element testing under controlled cyclic loading in undrained conditions. In this work, a total of 20 stress-controlled dynamic triaxial experiments were conducted on saturated specimens of clean sand to improve the understanding of the liquefaction phenomenon. The triaxial specimens were prepared at different relative densities in the range of 38 to 90% and subjected to varying cyclic stress ratios (CSR) with loading frequencies of 0.1 and/or 1 Hz. The experimental results indicated that under similar test conditions, the number of cycles needed for liquefaction was greater at 1 Hz than at 0.1 Hz, revealing that sand specimens exhibited higher liquefaction strength at higher loading frequencies. Furthermore, regardless of the cyclic loading frequency, the liquefaction resistance of sand increased with increasing densities.
Keywords: Liquefaction; Stress-controlled tests; Dynamic triaxial testing; Clean sand